2002
DOI: 10.3201/eid0806.010368
|View full text |Cite
|
Sign up to set email alerts
|

Three Drinking-Water–Associated Cryptosporidiosis Outbreaks, Northern Ireland

Abstract: Three recent drinking-water–associated cryptosporidiosis outbreaks in Northern Ireland were investigated by using genotyping and subgenotyping tools. One Cryptosporidium parvum outbreak was caused by the bovine genotype, and two were caused by the human genotype . Subgenotyping analyses indicate that two predominant subgenotypes were associated with these outbreaks and had been circulating in the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
160
2
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 216 publications
(176 citation statements)
references
References 13 publications
9
160
2
5
Order By: Relevance
“…Changes in the epidemiology are more readily observed and investigated (Smerdon et al, 2003;Hunter et al, 2003;Sopwith et al, 2005). Analytical epidemiological studies have identified specific risk factors for sporadic cases: contact with farmed animals for C. parvum and travel abroad, changing nappies and contact with another infected person for C. hominis (Hunter et al, 2004a) and linked species to socio-economic factors is not clear (Glaberman et al, 2002), and it is important that this is underpinned by routine species identification to establish the background epidemiology. The infecting species has been identified in a large number of outbreaks worldwide, and C. parvum and/or C. hominis are always involved Nichols et al, 2006a).…”
Section: Th Emop August 2008mentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in the epidemiology are more readily observed and investigated (Smerdon et al, 2003;Hunter et al, 2003;Sopwith et al, 2005). Analytical epidemiological studies have identified specific risk factors for sporadic cases: contact with farmed animals for C. parvum and travel abroad, changing nappies and contact with another infected person for C. hominis (Hunter et al, 2004a) and linked species to socio-economic factors is not clear (Glaberman et al, 2002), and it is important that this is underpinned by routine species identification to establish the background epidemiology. The infecting species has been identified in a large number of outbreaks worldwide, and C. parvum and/or C. hominis are always involved Nichols et al, 2006a).…”
Section: Th Emop August 2008mentioning
confidence: 99%
“…Further characterisation of Cryptosporidium oocysts from both patients and suspected sources and vehicles of transmission is an important investigative tool during outbreaks. Not only have potential sources been better defined, for example identifying human sewage as the potential contaminant over agricultural pollution (Glaberman et al, 2002) but also the relationship between source, supply and human cases and isolates circulating in the community in general (Zhou et al, 2003;Cohen et al, 2006;Anon 2006;Chalmers et al, 2008). However, Cryptosporidium presents three main problems for the isolation of DNA: 1) the robust nature of the oocysts, requiring a disruption step prior to DNA extraction; 2) the richness of PCR inhibitors in the sample matrix, requiring separation during DNA extraction and/or suppression during amplification; and 3) the low number of oocysts usually present in prospectively gathered and environmental samples.…”
Section: Th Emop August 2008mentioning
confidence: 99%
“…Sequences of parC and parE genes were the same as in a ciprofl oxacin-susceptible isolate tested. The association of the Cip-R phenotype with mutations in gyrA was confi rmed by transformation into the susceptible isolate by using appropriate PCR products (9). In addition to the common Thr91 → Ile substitution, the 3 Cip-R isolates were distinguishable by additional gyrA alterations or phenotypic and genotypic characteristics.…”
mentioning
confidence: 99%
“…and Cryptosporidium spp. [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. These outbreaks have often been associated with recreational water (lakes, swimming pools, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The major focus has been on water supply contaminated with enteric bacteria, virus and parasites from animals and humans [3][4][5][6][7][8][9], which have caused several large and serious outbreaks of intestinal infections [3][4][5][6][7][8][9]. These outbreaks have mainly been caused by Campylobacter spp., Escherichia coli, Norwalk-like virus, Giardia spp.…”
Section: Introductionmentioning
confidence: 99%